Profil Higher Order Thinking Skills dan Literasi Sains Siswa dalam Pembelajaran Inkuiri Terbimbing Berbantuan Virtual Lab: (Profile of Students' Higher Order Thinking Skills and Scientific Literacy in Virtual Lab Assisted Guided Inquiry) - Neng Yuli Hentian; Billyardi Ramdhan; Setiono Setiono (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the profile of students' higher order thinking skills and scientific literacy in guided inquiry learning. ) assisted by a virtual lab, seeing the relationship between higher order thinking skills and scientific literacy based on the data obtained, as well as knowing the increase in higher order thinking skills and scientific literacy based on class groupings. The method used is descriptive quantitative analysis. The research subjects were students of SMAN 1 Nagrak totaling 30 students. The sampling technique is purposive sampling using an instrument in the form of multiple choice questions. The results of this study show the percentage of HOTS with a percentage of 87% (excellent criteria), and 81% scientific literacy (very good criteria). The two abilities are not influenced by gender because the average percentage of the value of the two is not much different. higher order thinking skills correlated with scientific literacy at the sig value. 0.000 and correlation coefficient 0.684 with a strong relationship strength. Guided inquiry learning is suitable for student asor groups in improving students' higher order thinking skills and superior groups for improving scientific literacy. Key words: Higher Order Thinking Skills, Scientific Literacy, Guided Inquiry, Virtual Lab ABSTRAK Penelitian ini bertujuan untuk mengetahui profil higher order thinking skills dan literasi sains siswa pada pembelajaran inkuiri terbimbing (guided inquiry) berbantuan virtual lab, melihat hubungan higher order thinking skills dengan literasi sains berdasarkan data yang didapat, serta mengetahui peningkatan higher order thinking skils dan literasi sains berdasarkan pengelompokan kelas. Metode yang digunakan adalah analisis deskriptif kuantitatif. Subjek penelitian adalah siswa SMAN 1 Nagrak berjumlah 30 peserta didik. Teknik sampling yaitu purposive sampling dengan menggunakan instrumen berupa soal pilihan ganda. Hasil penelitian ini menunjukan presentase HOTS dengan presentase 87% (kriteria sangat baik), dan literasi sains 81% (kriteria sangat baik).Dari data tersebut disimpulkan HOTS dan literasi sains siswa dalam pembelajaran inkuiri terbimbing Â berbantuan virtual lab termasuk kedalam kriteria sangat baik. Kedua kemampuan tersebut tidak dipengaruhi oleh gender karena rata-rata presentase nilai keduanya tidak jauh berbeda. higher order thinking skills berkorelasi dengan literasi sains berada pada nilai sig. 0,000 dan correlation coefficient 0,684 dengan kekuatan hubungan kuat. Pembelajaran inkuiri terbimbing cocok untuk kelompok asor siswa dalam meningkatkan higher order thinking skills siswa dan kelompok unggul untuk meningkatkan literasi sains. Kata kunci: Higher Order Thinking Skills, Literasi Sains, Inkuiri Terbimbing (Guided Inquiry), Virtual Lab